2012
DOI: 10.1016/j.biortech.2012.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic cultivation of Chlorella vulgaris using industrial dairy waste as organic carbon source

Abstract: Growth parameters and biochemical composition of the green microalga Chlorella vulgaris cultivated under different mixotrophic conditions were determined and compared to those obtained from a photoautotrophic control culture. Mixotrophic microalgae showed higher specific growth rate, final biomass concentration and productivities of lipids, starch and proteins than microalgae cultivated under photoautotrophic conditions. Moreover, supplementation of the inorganic culture medium with hydrolyzed cheese whey powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
3
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(147 citation statements)
references
References 29 publications
(29 reference statements)
7
128
3
9
Order By: Relevance
“…Hence the result showed that there was some growth promoting factors in dairy waste so as to find higher biomass production than medium containing easily utilizable glucose as sole carbon source. Abreu (Abreu et al, 2012) reported the similar results in which the highest values of X max (3.58 g/L) and P max (0.43 g/L/d) using dairywater as cultivation medium. The results obtained above using the mixotrophic culture where hydrolyzed cheese whey powder solution is used which is comparable to our results.…”
Section: Disscussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Hence the result showed that there was some growth promoting factors in dairy waste so as to find higher biomass production than medium containing easily utilizable glucose as sole carbon source. Abreu (Abreu et al, 2012) reported the similar results in which the highest values of X max (3.58 g/L) and P max (0.43 g/L/d) using dairywater as cultivation medium. The results obtained above using the mixotrophic culture where hydrolyzed cheese whey powder solution is used which is comparable to our results.…”
Section: Disscussionsupporting
confidence: 55%
“…Organic carbon sources (as hexoses and pentoses) in dairy wastewater were used to facilitate the sustainability of biofuel industries (Abreu et al, 2012;Kothari et al, 2012;Prajapati et al, 2014;Srinivasan & Subramaniam, 2009;Wang et al, 2009). This capacitates the dairy industry to provide a technology to conserve water, an efficient and simultaneously aggrandize cost of waste water treatment of dairy industries .…”
Section: Introductionmentioning
confidence: 99%
“…In Chlorella vulgaris, mixotrophic culture with 1.0 percent glucose showed the highest lipid productivity compared to other growth conditions (Liang et al 2009). Abreu et al (2012) showed that mixotrophic cultivation of Chlorella vulgaris had higher specific growth rate, final biomass production and also higher lipid productivity. The biomass and lipid production of tested strains in mixotrophic culture were higher compared with other methods of culture especially with marine Chlorella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with organic carbon is mostly investigated and applied to boost algal lipid content. But a few studies documented enhancement of carbohydrate or starch content in Chlorella species under mixotrophy or heterotrophy (Abreu et al 2012;Yeh and Chang 2012;Li et al 2015a). In contrast, switching from photoautotrophy did not benefit starch accumulation in C. reinhardtii without stressing the cells (Ball et al 1990).…”
Section: Inorganic and Organic Carbonmentioning
confidence: 97%